Paradigm Changes in Proving Unlawful Acts in Corruption Crimes Following Constitutional Court Decision Number 25/PUU-XIV/2016 - Sulaiman, Abdullah; Cahyadi, Dedy; Iwansyah; Prasetyo, Rahmad; Pambudi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The Constitutional Court Decision Number 25/PUU-XIV/2016 has marked an important turning point in the enforcement of corruption law in Indonesia, especially in proving the element of state financial loss. Before this decision, the formal approach that emphasized procedural violations without the need to prove actual losses was still commonly used. However, after the decision, the legal interpretation shifted towards a material approach that required actual loss to prove corruption. This change has quite complex legal and practical consequences, ranging from increasing the burden of proof for public prosecutors, and dependence on the results of audits of state financial institutions to technical challenges in coordination between law enforcers. This study comprehensively examines the development of legal interpretation before and after the Constitutional Court decision, and its impact on the evidentiary process, and formulates strategic steps that can be taken to strengthen the effectiveness of corruption eradication while ensuring legal certainty for the parties.